2003
DOI: 10.1111/j.0014-3820.2003.tb01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding, Developmental Stability, and Canalization in the Sand Cricket Gryllus Firmus

Abstract: Inbreeding, the mating of close relatives, is known to have deleterious effects on fitness traits in organisms. Developmental stability (DS) and canalization may represent two processes that allow an organism to maintain a stable development that will produce the fittest phenotype. Inbreeding is thus expected to affect either DS or canalization. We tested if inbreeding affects DS and canalization using an inbreeding experiment on the cricket Gryllus firmus. We compared mean length, fluctuating asymmetry (as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…Willmore, Klingenberg & Hallgrimsson (2005) analysed the relationship between FA and environmental variance in the skull of rhesus macaque Macaca mulatta, reporting significant but low correlations. Studies on wing shape reported high correlations in Drosophila melanogaster, tsetse fly (Glossina palpalis gambiensis) and bumblebee (Bombus empatiens) (Klingenberg & McIntyre, 1998;Klingenberg et al, 2001;Santos, Iriarte & Céspedes, 2005;Breuker, Patterson & Klingenberg, 2006) as well as for other traits in 11 invertebrate species (Clarke, 1998); whereas the opposite result was found for cricket limbs (Reale & Roff, 2003). Studies involving the alteration of the heat shock protein 90 (Hsp90) considered a specific mechanism for canalization (Rutherford & Lindquist, 1998;Rutherford, 2000), by either a mutational or pharmacological approach, resulted in an increase of phenotypic variance but did not show any increase of FA, leading to the conclusion that two distinct mechanisms for DS and canalization exist (Milton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Willmore, Klingenberg & Hallgrimsson (2005) analysed the relationship between FA and environmental variance in the skull of rhesus macaque Macaca mulatta, reporting significant but low correlations. Studies on wing shape reported high correlations in Drosophila melanogaster, tsetse fly (Glossina palpalis gambiensis) and bumblebee (Bombus empatiens) (Klingenberg & McIntyre, 1998;Klingenberg et al, 2001;Santos, Iriarte & Céspedes, 2005;Breuker, Patterson & Klingenberg, 2006) as well as for other traits in 11 invertebrate species (Clarke, 1998); whereas the opposite result was found for cricket limbs (Reale & Roff, 2003). Studies involving the alteration of the heat shock protein 90 (Hsp90) considered a specific mechanism for canalization (Rutherford & Lindquist, 1998;Rutherford, 2000), by either a mutational or pharmacological approach, resulted in an increase of phenotypic variance but did not show any increase of FA, leading to the conclusion that two distinct mechanisms for DS and canalization exist (Milton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While the effect of intraindividual genetic diversity on sensitivity to environmental variation has been suggested in earlier work (Mitton and Grant 1984;Deng 1997;Réale and Roff 2003;Kristensen et al 2005), this study provides novel insights in several respects. First, whereas the necessity for detailed pedigrees has largely constrained previous studies to inbred laboratory lines, the use of molecular marker-derived estimates of relatedness in this study allowed us to examine naturally occurring variation in inbreeding.…”
Section: Discussionmentioning
confidence: 65%
“…In particular, inbred offspring often exhibit greater morphological variation compared to outbred individuals (Yezerinac et al 1992;David et al 1997;Deng 1997;Réale and Roff 2003). And while theory predicts that natural selection should strongly favor behaviors that minimize inbreeding (Blouin and Blouin 1988;Pusey and Wolf 1996), matings between relatives might nevertheless occur when individual mate choice is constrained, suggesting that any effect of inbreeding on developmental variation should be particularly relevant in natural systems where mate sampling is costly (e.g., Johnsen et al 2000;Foerster et al 2003) and opportunities to breed are limited (e.g., Keller and Arcese 1998;Kruuk et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The general idea has been that different underlying processes govern developmental stability and canalization. However, the results from empirical tests (studied using patterns of phenotypic variation) have been contradictory, some studies indicating that developmental stability and canalization are separate phenomena governed by separate mechanisms (Waddington 1957;Rutherford and Lindquist 1998;Debat et al 2000;Milton et al 2003;Réale and Roff 2003) while others have indicated that they represent similar phenomena that at least partly share underlying developmental processes (Clarke 1993(Clarke , 1998Klingenberg and McIntyre 1998;Woods et al 1999;Hallgrímsson et al 2002;Santos et al 2005;Breuker et al 2006;Debat et al 2006). A recent study by Breuker and colleagues (2006) compares among-individual variation with FA in the wings of 115 different strains of Drosophila melanogaster.…”
Section: Developmental Stability-measurement Through Patterns Of Varimentioning
confidence: 99%